Pengaruh Kualitas Pelayanan Dan Tarif Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Pengguna Jasa DHL Global Forwarding (Studi pada pengguna jasa DHL Di Kota Semarang) - Robiul Hasanah; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
In the development of the world business now cargo transport services develops very rapidly including traffic export goods imports. DHL Global Forwarding is a company which moves in the fields of services import export , who over a period of years 2011-2014 always ranked to 4 top brand index of shipping services in indonesia; percentage tending to increased but could not surpass delivery company services which other. During that period the amount of service users PT.DHL Global Forwarding the branch of semarang continues to decrease. The condition is demanding the company back to evaluate the quality of service and the fare given the satisfaction of users for the sake of .The purpose of this research is knowing the influence of the quality of the waiters and tariff users against satisfaction in DHL Global Forwarding semarang city. Type of research that is used is explanatory research, with a sample of 100 respondents who uses services DHL Global Forwarding in semarang cityData collection method is documentation and the questionnaire, the method of analysis namely the instrument ( the validity and reliability test), analysis table cross, regression test , the determination , uji-t , uji-f and analysis the using spss 16 for windows.The result showed that any impact positively and significant quality of services and rates of customer loyalty indirectly through the customer satisfaction as variable intervening, because direct effect < indirect effect.So, the conclusion increased customer loyalty could be achieved through improving the quality of service, giving the fare cheap and satisfaction high service.Recommendations to research it is the first, develop a communication with our customers especially delay to inform dispatches on the objective of control of the company; second, always motivate employees to improve their services.